Intravenous versus oral rehydration during a brief period: responses to subsequent exercise in the heat - Casa, D. J.; Maresh, C. M.; Armstrong, L. E.; Kavouras, S. A.; Herrera, J. A.; Hacker, F. T.; Keith, N. R.; Elliott, T. A. (Medicine & Science in Sports & Exercise, 2000)
Purpose: The purpose of this study was to assess whether a brief period (20 min) of intravenous (IV) fluid rehydration versus oral rehydration differentially affects cardiovascular, thermoregulatory, and performance factors during exhaustive exercise in the heat. Methods: Following dehydration (-4% of body weight), eight nonacclimated highly trained cyclists (age = 23.5 ± 1.2 yr; V(dot)O2peak = 61.4 ± 0.8 mL·kg·min-1; body fat = 13.5 ± 0.6%) rehydrated and then cycled at 70% V(dot)O2peak to exhaustion in 37°C. Rehydration (randomized, cross-over design) included: 1) CONTROL (no fluid), 2) DRINK (oral rehydration, 0.45% NaCl) equal to 50% of prior dehydration, and 3) IV (intravenous rehydration, 0.45% NaCl), equal to 50% of prior dehydration. Thus, in the DRINK and IV treatments subjects began exercise (EX) at -2% of body weight. Results: Exercise time to exhaustion was not different (P = 0.07) between DRINK (34.9 ± 4 min) and IV (29.5 ± 3.5 min), but both were significantly (P < 0.05) longer than CONTROL (18.9 ± 2.7 min). Plasma volume was better (P < 0.05) restored during IV than CONTROL and DRINK at pre-exercise and 5 min EX, but different (P < 0.05) from only CONTROL at 15 min EX. Plasma lactate during DRINK was lower (P < 0.05) than IV at 15 min EX and postexercise. Heart rate during CONTROL was greater (P < 0.05) than DRINK and IV from 0-8 min EX, and greater (P < 0.05) than DRINK from 10-14 min EX. Rectal temperature during DRINK was less (P < 0.05) than IV from 0-24 min EX. Mean weighted skin temperature during DRINK was less (P < 0.05) than IV from 4-12 min EX. Conclusions: Thus, despite no statistically significant performance differences between DRINK and IV, it appears that certain physiological parameters were better maintained in the DRINK trial, and the trend toward performance differences may be important to elite athletes.